Glycogen-nucleic acid constructs for gene silencing in multicellular tumor spheroids. (September 2018) - Wojnilowicz, Marcin; Besford, Quinn A.; Wu, Yun-Long; Loh, Xian Jun; Braunger, Julia A.; Glab, Agata; Cortez-Jugo, Christina; Caruso, Frank; Cavalieri, Francesca
Abstract: The poor penetration of nanocarrier-siRNA constructs into tumor tissue is a major hurdle for the in vivo efficacy of siRNA therapeutics, where the ability of the constructs to permeate the 3D multicellular matrix is determined by their physicochemical properties. Herein, we optimized the use of soft glycogen nanoparticles for the engineering of glycogen-siRNA constructs that can efficiently penetrate multicellular tumor spheroids and exert a significant gene silencing effect. Glycogen nanoparticles from different bio-sources and with different structural features were investigated. We show that larger glycogen nanoparticles ranging from 50 to 80 nm are suboptimal systems for complexation of nucleic acids if fine control of the size of constructs is required. Our studies suggest that 20 nm glycogen nanoparticles are optimal for complexation and efficient delivery of siRNA. The chemical composition, surface charge, and size of glycogen-siRNA constructs were finely controlled to minimize interactions with serum proteins and allow penetration into 3D multicellular spheroids of human kidney epithelial cells and human prostate cancer cells. We introduced pH sensitive moieties within the construct to enhance early endosome escape and efficiently improve the silencing effect in vitro . Glycogen-siRNA constructs were found to mediate gene silencing in 3D multicellular spheroids causing ∼60% specific gene silencing. The optimized construct exhibited an in vivo circulation lifetime of 8 h in mice, with preferential accumulation in the liver. No accumulation in the kidney, lung, spleen, heart or brain, or signs of toxicity in mice were observed. Our results highlight the potential for screening siRNA nanocarriers in 3D cultured prostate tumor models, thereby improving the predictive therapeutic efficacy of glycogen-based platforms in human physiological conditions. Graphical abstract: Image 1